Gene expression, characterization and in silico studies of delta fatty acid desaturases - Abd Halim, Nur Farah Anis (2022)
Fatty acid desaturases (FAD) catalyze desaturation reactions by the insertion of double bonds into the fatty acyl chain, producing unsaturated fatty acids. Though soluble FAD has been studied widely in higher living organisms, there are very limited studies of membrane FAD due to the difficulty of generating recombinant desaturases as well as their higher tendency to become toxic cells. Membrane FAD is predominant, as they play a crucial role in the synthesis of polyunsaturated fatty acids and offer nutritional benefits to humans. In this study, a range of fatty acid desaturases consisting of Δ6, Δ12, and Δ15 FAD was chosen from different organisms which exists abundantly to pave way for characterization. Δ6 FAD was isolated, and PCR amplified from Anoxybacillus geothermalis, cloned in pGEX-4T1 vector and expressed in E. coli BL21 (DE3) with the expected amplicon of 1104 bp encoding for 368 amino acids obtained with the restriction enzymes BamHI and EcoRI. The 1230 bp open reading frame of Δ12 FAD coding for 410 amino acid sequences from Brassica napus, had been successfully synthesized. It was cloned in pET-51b(+) with restriction enzymes SalI and NotI and expressed in E. coli BL21 (DE3) at 37 °C in intracellular and inclusion body fractions when induced with 0.5 mM IPTG, with an expected size of 49 kDa. Recombinant Δ12 FAD was successfully purified in two steps of chromatography: hydrophobic interaction chromatography (HIC) and ion exchange chromatography (IEX) with resin Butyl-S Sepharose 6 Fast Flow and SP Sepharose Fast Flow, respectively with a total protein yield of 1.55 mg/mL. The characterization of recombinant Δ12 FAD revealed desaturase activity of Δ12 FAD could produce linoleic acid from oleic acid at a retention time of 17.6 with a composition of 47%. Analysis of circular dichroism (CD) showed Δ12 FAD was made up of 47.3% and 0.9% of α-helix and β-sheet secondary structures, respectively. The predicted Tm value was 50.2 °C. Δ15 FAD had been synthesized from Synechocystis sp., a cyanobacterium and cloned in pET-51b(+) with restriction enzyme SalI and NotI with expected size around 1155 bp coding for 385 amino acid sequences. The protein was expressed in intracellular and inclusion body fractions in E. coli BL21 (DE3) at 30 °C when it was induced by 1.0 mM IPTG with expected size of 47 kDa. Recombinant Δ15 FAD was purified in two steps of chromatography: Hydrophobic Interaction Chromatography (HIC) and Ion Exchange Chromatography (IEX) with resin Butyl-S Sepharose 6 Fast Flow and SP Sepharose Fast Flow, respectively with the total protein yield of 1.28 mg/mL. The characterization of recombinant Δ15 FAD revealed desaturase activity of Δ15 FAD could produce α-linoleic acid at retention time of 22.3 with the composition of 32%. Characterization of semi-purified Δ15 FAD revealed the optimal temperature was 40 °C with 1 mM preferred substrate concentration of linoleic acid. The analysis of CD showed Δ15 FAD was made up of 51.8 % and 2.2 % of α- helix and β-sheet secondary structures, respectively. The predicted Tm value for Δ15 FAD was 49 °C. The three-dimensional (3D) structure of each recombinant protein was predicted using YASARA software and verified against validation tools; ERRAT2, Verify3D, and PROCHECK. Among the three FAD, Δ15 FAD structure displayed the best validation score. In conclusion, Δ6 FAD had been isolated and expressed in E. coli BL21 (DE3), whereas Δ12 FAD and Δ15 FAD had been successfully synthesized, overexpressed, purified and characterized to enhance the way towards understanding and modification of membrane protein